THE INFLUENCE OF TALENT MANAGEMENT AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS THE INTERVENING VARIABLE ON PT KERETA API INDONESIA (PERSERO) DIVISION REGIONAL I SUMUT - Rhilo Ahadi Rahman; Fajar Pasaribu; Hazmanan Khair; Satria Tirtayasa (Jurnal Ekonomi, 2023)
The purpose of this research conducted at PT Kereta Api Indonesia (Persero) Divre I North Sumatra is to determine the effect of talent management and knowledge management on employee performance with employee engagement as an intervening variable. the effect of talent management and knowledge management on employee performance simultaneously and partially, as well as the effect of employee engagement on employee performance in part, and to find out how these factors affect employee engagement. The participants in this study were. By using the census method, which turns the entire population into a sample, this sample can be identified. Data collection used questionnaires, and multiple linear regression and path analysis were used to analyze the results. Talent management has an effect on employee engagement, knowledge management has an effect on employee engagement, talent management and knowledge management have an effect on employee engagement, and talent management and knowledge management have no effect on employee performance, according to the findings of this study. Through employee engagement, talent management has a greater direct impact on employee performance than it does indirectly through talent management. And ast is employee engagement has a smaller indirect impact on employee performance than knowledge management directly affects employee performance.